The effect of UF addition on the properties of citric acid-starch bonded particleboard - Abdullah, Ummi Hani; Salim, Sabiha; Abdullah, Luqman Chuah; Hamid, Norul Hisham; Zhou, Hua Xu; Lee, Seng Hua (Forestry Department Peninsular Malaysia, 2024)
Citric acid and starch have attracted considerable interest as potential modifiers for ureaformaldehyde (UF) adhesives, owing to their capability to improve performance and promote environmental sustainability. This study examines the impact of varying urea-formaldehyde (UF) content added to a citric acid-tapioca starch adhesive system on the performance of rubberwood particleboard. The total resin content was set at 10%, with the adhesive composed of a mixture of citric acid (CA) and tapioca starch in a 75/25 ratio. UF was added to the adhesive in three different formulations: 2%, 5%, and 10% of the total resin content. The resulting particleboards were then tested for thickness swelling (TS), water absorption (WA), internal bond strength (IB), modulus of elasticity (MOE), and modulus of rupture (MOR). The findings indicate that increasing UF content improves the mechanical properties, such as the modulus of rupture (MOR) and modulus of elasticity (MOE). However, higher UF content also negatively impacts the physical properties, resulting in greater thickness swelling (TS) and water absorption (WA), which may compromise the overall dimensional stability and internal bond (IB) strength. The study concludes that UF content of around 5% offers an optimum property, achieving strong mechanical performance (IB = 0.207 N/mm², MOR = 8.35 MPa, and MOE = 1645.15 MPa) while managing physical properties within acceptable ranges (TS = 17.5120.15%, WA = 87.8793.43%, Density = 565.36 kg/m³).